PENAMPILAN 54 FENOTIPE GALUR MUTAN KEEMPAT KACANG HIJAU (Vigna radiata L.) LOKAL KAMPAR HASIL MUTASI KOLKISIN - Elfrida Oktavia; Herman Herman; Dewi Indriyani Roslim (DINAMIKA PERTANIAN, 2013)
This research aimed to evaluate and select the 54 phenotype for fourth mutant galur of Kampar local mung bean resulting kolkisin mutation based on appearance of phenotype and agronomy plant. The research was carried out at Biological farm of FMIPA Riau University from April to September 2013. The randomized Block Design was used with one factor consisting of 54 treatments and 5 repetitions. Of the 54 galurs tested, it was found that 5 galur had the characteristic based on the observed parameter, namely PRCM_2153 galur, PRCM_2353 galur, PRCM_3314 galur, PRCM_3514 galur, and PRCM_3934 galur.